# Derivative of Exponential at Zero/Proof 1

Jump to navigation
Jump to search

## Theorem

Let $\exp x$ be the exponential of $x$ for real $x$.

Then:

- $\displaystyle \lim_{x \mathop \to 0} \frac {\exp x - 1} x = 1$

## Proof

For all $x \in \R$:

- $\exp 0 - 1 = 0$ from Exponential of Zero

- $\map {D_x} {\exp x - 1} = \exp x$ from Sum Rule for Derivatives

- $D_x x = 1$ from Derivative of Identity Function.

Its prerequisites having been verified, Corollary 1 to L'Hôpital's Rule yields immediately:

- $\displaystyle \lim_{x \mathop \to 0} \frac {\exp x - 1} x = \lim_{x \mathop \to 0} \frac {\exp x} 1 = \exp 0 = 1$

$\blacksquare$

## Sources

- 1977: K.G. Binmore:
*Mathematical Analysis: A Straightforward Approach*... (previous) ... (next): $\S 14.5 \ (3) \ \text{(i)}$